Laughter as a social rejection cue: Gelotophobia and transient cardiac responses to other persons' laughter and insult. (1st July 2014) - Papousek, Ilona; Aydin, Nilüfer; Lackner, Helmut K.; Weiss, Elisabeth M.; Bühner, Markus; Schulter, Günter; Charlesworth, Canice; Freudenthaler, H. Harald
Abstract Other persons' laughter, normally perceived as a signal that persons are friendly and inviting others to approach, can also be perceived as a cue of social rejection. In this study, prerecorded laughter was placed in a realistic and personally relevant context, and participants' responses were related to gelotophobia, a trait predisposing to perceiving laughter as a cue of social rejection. Individuals with gelotophobia showed marked heart rate deceleration in response to the laughter stimulus, possibly indicating a "freezing‐like" response. Moreover, cardiac responses to anger provocation by overtly insulting statements indicated heightened aggressive anger in response to cumulated social threat. The study adds to recent research showing specific cardiac responses to social rejection and to the literature on social rejection sensitivity by demonstrating the value of using well interpretable physiological measures in this research context.